Potensi Komoditas Kopi Indonesia Pada Pasar Asean Dengan Malaysia Sebagai Negara Tujuan Ekspor - Ramadhani, Dhea Putri (Peneliti.net, 2023)
Writing this article aims to find out whether Malaysia is a suitable destination country for coffee commodities. The purpose of this writing, apart from finding out that Malaysia is suitable to be an export destination country, is to map. The results obtained are that Malaysia has great potential if it becomes an export destination country because the trade balance is negative, which means knowing whether Indonesia is able to enter and compete in the international market. The writing of this article uses a quantitative method with a descriptive method so that data from several sources such as the Central Bureau of Statistics and Trade still require receipt of imported products from other countries. One of Indonesia's toughest competitors in the ASEAN market for this coffee commodity is Vietnam because Vientam is one of the largest coffee exporting countries. Indonesian coffee is able to compete in the international market because if you look at the data from the Central Bureau of Statistics, Indonesia does not only export to ASEAN countries but also exports to other developed countries. So Indonesia has a great opportunity to be in the international market, but Indonesian coffee products must always improve their quality so that export demand does not decrease. With the assistance from the government to assist coffee farmers in empowering coffee, it can improve the quality of Indonesian coffee commodities.